Fomo at The Blackpink Concert Causes Cyberbalkanization and Polarization Between Fans and Non-Fans - Lucky Khalisha; Vera Wijayanti Sutjipto; Maulina Larasati Putri (Journal of Social Research, 2025)
This study discusses the phenomenon of cyberbalkanization that arises from debates between Indonesian netizens regarding the Blackpink concert and the term "Fomo" used to describe the behavior of non-fans who attended the concert. This study aims to highlight the importance of awareness of the phenomenon of cyberbalkanization and how this can affect the dynamics of interaction between groups on social media, especially in the context of cyberbullying behavior, hate speech, and fragmentation of views among netizens who interact with each other on social media platforms. That way it can be related to the research title of the researcher, namely cyberbalkanization and polarization that occurs between Blackpink fans and non-fans, caused by the "Fomo" phenomenon which was carried out by many non- fans during the Blackpink concert in Jakarta, which both groups need to be aware of. because it can affect the dynamics of interaction between groups on social media. This study uses text analysis as a data collection method, involving seven informants who are fans and non-fans of Blackpink, and considers comments on social media about "Fomo" at Blackpink concerts. This research also refers to previous literature reviews related to cyberbalkanization, polarization on social media, and communication within the Blackpink fan community. This phenomenon resulted in a polarization of views among netizens who were divided into two camps with different perspectives regarding the presence of non-fans at concerts.